Hybrid nanocomposites of a fluorescent block copolymer and quantum dots: an efficient way for energy transfer - Moura, I. (2017)
Forster resonance energy transfer (FRET) phenomenon has great potential in several applications, whose efficiency is dependent on the energy transfer between a suitable pair of fluorophores. In this work, a new block copolymer, PS-b-PS(co-pyren-1-yl), with fluorescent properties, was synthetized and used as donor component in the fluorophores pair copolymer/cadmium telluride quantum dots (CdTe QDs). Thus, water-soluble CdTe QDs, previously transferred into organic phase, by replacing the stabilizer ligands, thioglycolic acid by 1-dodecanethiol (1-DDT), were used to prepare a new hybrid nanocomposite. FRET studies between the fluorescent copolymer and CdTe-DDT QDs revealed that this fluorophores pair can experience FRET with an efficiency of 48%, being an efficient antenna system for light harvesting applications.